A rare case of genital myiasis in genital prolapse - Kumari, Asha; Sudha Gandhi; Savitri Verma; Yukti Gaur; Neeraj Chowdhary (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Genital myiasis is an infestation by fly larvae in genital organs, where they feed and develop as parasites. They can cause severe infection, inflammatory reaction and can be linked to psychiatric disturbances. Commonly cutaneous, ophthalmic, auricular and nasopharyngeal myiasis are seen, with genital myiasis being a rare condition. We reported a case of an 82-year-old postmenopausal female who presented with the complaint of intense pain in genital region. After clinical evaluation she was clinically diagnosed as a case of genital myiasis of prolapsed uterus. Myiasis of the genital organ is a rare clinical entity. Good personal hygiene and proper sanitary conditions are very crucial for prevention of myiasis.